The Influence of People's Business Credit (KUR) on the Income of Food Traders at Bank BRI Simpang IV Sipin - Parameswari, Mutia Yasmin; Zami, Zam; Parkhusrt, Helen; Pasla, Bambang Niko (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: This research aims to determine the effect of People's Business Credit (Kur) on the income of customers of food traders at Bank Bri Simpang IV Sipin. Research Methods: A quantitative approach with a total of 94 respondents is used, determined using the Slovin formula with a margin of error of 10%. The sampling technique used was purposive sampling with the criteria of KUR customers at BRI Simpang IV Sipin. Data analysis was carried out through validity, reliability, classical assumption tests, and simple linear regression using the partial coefficient test (t test) and using the SPSS 25.0 software application. Finding/Results: The research results show that simultaneously people's business credit (KUR) has a significant effect on the income of food customers at BRI Simpang IV Sipin. The coefficient of determination shows that the variable can explain the behavior of BRI Simpang IV Sipin customers. Conclusion: It can be concluded that the average increase after receiving KUR has a positive impact on business development and the economic capabilities of business actors.